(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
قمنا في هذا البحث بدراسة تأثير درجة حرارة الركيزة على كل من الناقلية الكهربائية المظلمة والناقلية الكهرضوئية للأفلام الرقيقة المحضرة من السيلكون المهدرج غير المتبلور (a-Si:H) بطريقة التذرية، وعرضنا نتائج حساب نسبة الناقلية الضوئية إلى الناقلية الكهربائية المظلمة. ومن ثم عينا درجة الحرارة الحدية للركيزة الموافقة للقيمة العظمى لنسبة الناقلية الضوئية إلى الناقلية المظلمة والتغير الحاد في متحولات الناقلية المظلمة للسيلكون المهدرج غير المتبلور. علاوة على ذلك عرضنا نتائج دراسة مقاومة تماس الجملة المكونة من الفلم الرقيق a-Si:H/النيكل عند تغير درجة حرارة الركيزة. In this search, we studied the influence of the substrate temperature on the electrical and photo-conductivities of thin films prepared from amorphous hydrogenated silicon (a-Si:H) by sputtering, Details of the results of the calculation of the photoconductivity to the dark conductivity ratio are shown. Then, the critical substrate temperature, which consists of maximum value of photoconductivity to dark conductivity ratio and critical change of dark conductivity parameters of amorphous hydrogenated silicon, is also determined. In additional, the results of studying the contact resistance of thin film/nickel system at the substrate temperature change are shown.